PENGARUH SENAM LANSIA TERHADAP TINGKAT INSOMNIA PADA LANSIA DI YAYASAN BINA BHAKTI SASANA TRESNAWHERDA CARITAS BEKASI - Ernauli Meliyana; Siti Maria Ulfa (Universitas Malahayati Lampung, 2019)
ABSTRACT:THE INFLUENCE OF ELDERLY GYMNASTICS ON INSOMNIA LEVELS IN THE ELDERLY IN BINA BHAKTI FOUNDATION SASANA TRESNA WHERDA CARITAS BEKASI Background: Elderly is the last stage of life cycle in humans, where the need for health promotion efforts, both promotive and preventive, in order to maintain and improve the quality of life of the elderly. The elderly is someone who has reached the age of 60 years, which is a gradual process of causing cumulative changes, such as decreased endurance and the quality of life of the elderly.Purpose: Objective is to know the influence of elderly gymnastics on insomnia level in elderly at Yayasan Bina Bhakti Sasana Tresna Wherda Caritas Bekasi.Methods: The design used in this study was Quasi Experiment test and post test nonequivalent control group